FUNGSI HURUF أن DALAM Al-QUR’AN - Pathurahman, Wihda Islami (Departemen Pendidikan Bahasa Arab, 2019)
This research is motivated by the phenomenon of the letter Ø£Ù† in the Qur'an surah Al-A`rÄf which is not in accordance with the basic theories of Arabic linguists regarding the letter Ø£Ù†. Researchers use the content analysis method. Based on research that has been done, it was found that in the Al-A`rÄf letter there are several syntactic functions of Mu muwal muawwal from the letter Ø£Ù† with the words afterwards. The syntactic functions found are found in three i`rÄb, namely rafa`, naá¹£ab, and jar. From i`rÄb rafa` there are those who occupy the positions of fÄ`il, mubtada, isim ÙƒØ§Ù†, and khabar mubtada; in i`rÄb naá¹¡ab some occupy the positions of maf`Å«l bih, khabar ÙƒØ§Ù† and his brothers, maf`Å«l li ajlih, mustaá¹¡nÄ muttaá¹£il, and ma`á¹Å«f to isim maná¹£Å«b; in i`rÄb jar there are majrÅ«r by jar letters, domiciled as muá¸Äf ilaih, and ma`á¹Å«f to isim majrÅ«r.